ANALISIS EMPIRIS KURVA PHILLIPS PADA DUA KLASIFIKASI PENDAPATAN PERIODE 1990-2011 - , MAGFIRAH KRITANTYA MUTIA A.; , Prof. Dr. Samsubar Saleh, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the relationship between inflation and unemployment in 10 countries which classified in two categories: Upper Middle Income and Lower Middle Income for periods 1990-2011. The question regarding the new theories of Phillips Curve is, âIs the traditional Phillips Curve still reliable in developing countries?â. To answer this question, we use panel data method with quadratic variable to estimate the model in two income classification and do some treatment tests for data. Overall, we found support that Lower Middle Income countries still have negative relationship between inflation and unemployment, so that Phillips Curve is still reliable in Lower Middle Income countries. Meanwhile, Upper Middle Income countries now have the positive relation between inflation and unemployment. We also found that real interest rates and money supplies are significant factors which can affect inflation rates in the country.